Território e trajetória Krenak: o olhar geográfico de uma disputa de narrativas - Carvalho, Julia Araujo [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This document consists of a monograph at the end of the course, whose theme comprised scientific initiation research financed by FAPESP. The results of a five-year learning and research process can be seen below, of which two years were dedicated to the elaboration and development of a project that aimed to identify and assimilate the process of territorialization and deterritorialization of the People Krenak, resident in the Indigenous Land India Vanuíre, located in the Municipality of Arco Íris, SP, in order to understand the identity and how it is maintained, as well as to find, jointly with the indigenous group, strategies to strengthen Krenak identity through methodological principles proposed by Action Research. The investigative process involved a dense documentary and bibliographic analysis, in addition to field visits and collection of narratives. Among the main advances brought about by research on the theme, we point out: the establishment of a timeline that relates the processes of territorial movement Krenak with the political contexts in force from the end of the 17th century to the present; the discursive link between the Krenak history and trajectory told by official sources and the Krenak history and trajectory told by themselves. History that very recently started to convey the collective imagination through the words of Ailton Krenak and Edson Krenak; the emergence of a documentary repertoire focusing on territorialized Krenak in the Vanuíre Indigenous Land; an approach to the concept of Territory for the Krenak and; a brief analysis of the Common Base National Curriculum regarding the indigenous theme. We invite you now to read this document that compiles the trajectory, bearing in mind the following questions: What is Krenak's understanding of 'territory'? Is there a relationship between government interests and positions and violence against indigenous peoples? And the last and, perhaps more difficult questioning, is it possible to measure the impact that the arrival of Europeans from the 15th century onwards and their subsequent actions, had on the culture of the original peoples today, especially for the Krenak?

Este documento es una monografía de conclusión de licenciatura, cuyo tema fue la investigación de iniciación científica financiada por la FAPESP. A continuación se muestran los resultados de un proceso de aprendizaje e investigación de cinco años, de los cuales dos se dedicaron a la elaboración y desarrollo de un proyecto que tuvo como objetivo identificar y asimilar el proceso de territorialización y desterritorialización del pueblo Krenak, residente en la Tierra Indígena India Vanuíre, ubicada en el Municipio de Arco-Iris, SP, con el fin de comprender la identidad y cómo se mantiene, así como encontrar en conjunto con el grupo indígena, estrategias para fortalecer la identidad Krenak a través de principios metodológicos propuestos por la Pesquisa Acción. El proceso de investigación implicó un denso análisis documental y bibliográfico, además de visitas de campo y recopilación de narrativas. Entre los principales avances que ha generado la investigación sobre el tema, destacamos: el establecimiento de una línea de tiempo que relaciona los procesos del movimiento territorial Krenak con los contextos políticos vigentes desde finales del siglo XVII hasta la actualidad; el vínculo discursivo entre la historia y trayectoria Krenak contada por fuentes oficiales y la historia y trayectoria Krenak contada por ellos mismos. Historia esa que muy recientemente empezó a habitar el imaginario colectivo a través de las palabras de Ailton Krenak y Edson Krenak; la aparición de un repertorio documental centrado en los Krenak territorializados en la Tierra Indígena de Vanuíre; un enfoque del concepto de Territorio para los Krenak y; un breve análisis del Currículo Nacional de Base Común sobre el tema indígena. Te invitamos ahora a leer este documento que recopila la trayectoria antes mencionada, teniendo en cuenta las siguientes preguntas: ¿Qué entiende Krenak por 'territorio'? ¿Existe una relación entre los intereses y posiciones del gobierno y la violencia contra los pueblos indígenas? Y el último y, quizás más difícil cuestionamiento, ¿es posible medir el impacto que la llegada de los europeos a partir del siglo XV y sus acciones posteriores, tuvo en la cultura de los pueblos originarios de hoy, especialmente para los Krenak?

Este documento consiste em uma monografia de conclusão de curso, cujo tema compôs pesquisa de iniciação científica financiada pela FAPESP. A seguir poderão ser apreciados os resultados de um processo de aprendizado e investigação que teve cinco anos de duração, dos quais, dois anos foram dedicados a elaboração e desenvolvimento de um projeto que teve por objetivo identificar e assimilar o processo de territorialização e desterritorialização do Povo Krenak, residente na Terra Indígena Índia Vanuíre, localizada no Município de Arco Íris, SP, de modo a compreender a identidade e como esta se mantem, bem como encontrar de forma conjunta com o grupo indígena, estratégias de fortalecimento da identidade Krenak por meio de princípios metodológicos propostos pela Pesquisa-Ação. O processo investigativo envolveu uma densa análise documental e bibliográfica, além de visitas a campo e coleta de narrativas. Dentre os principais avanços propiciados pela pesquisa acerca da temática pontuamos: o estabelecimento de uma linha temporal que relaciona os processos de movimentação territorial Krenak com os contextos políticos vigentes desde o fim do Século XVII até o presente; a vinculação discursiva entre a história e trajetória dos Krenak contada pelas fontes oficiais e a história e trajetória Krenak contada pelos próprios. História que muito recentemente passou a veicular o imaginário coletivo através das palavras de Ailton Krenak e Edson Krenak; o surgimento de um repertório documental com enfoque nos Krenak territorializados na Terra Indígena Vanuíre; um acercamento da concepção de Território para os Krenak e; uma breve análise da Base Nacional Comum Curricular quanto à temática indígena. Os convidamos agora a ler esta monografia que compila a trajetória supracitada, tendo em mente os seguintes questionamentos: Qual a compreensão Krenak de ‘território’? Existe relação entre os interesses e posicionamentos governamentais e a violência contra os povos originários? E o último e, talvez mais difícil questionamento, é possível mensurar o impacto que, a chegada dos europeus a partir do século XV e suas posteriores ações, tiveram na cultura dos povos originários na atualidade, sobretudo para os Krenak?
Territorio y trayectoria Krenak: la mirada geografica de una disputa narrativa
Keywords: Territory; Dispute of narratives; Action Research; Decolonity; Territorio; Disputa narrativa; Pesquisa Acción; Território; Krenak; Disputa de narrativas; Decolonidade; Pesquisa-Ação